2020
DOI: 10.3389/feart.2020.00122
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms Associated With Dust on Alpine Snow

Abstract: We investigated snow microstructure and microbial composition from snow samples collected from western Colorado, a region that experiences frequent dust-on-snow deposition events. We developed a methodology to quantify the amount, size, and location of dust particles within the snow matrix through analysis of X-ray micro-computed tomography data. Concurrently, we determined the microbial composition in sampled dust layers through DNA sequencing. We found that dust particles were generally embedded in the snow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Similar to previous studies, we observed significant variation in microbial community composition between years ( Chuvochina et al, 2011 ; Pittino et al, 2018 ; Els et al, 2020 ) and sites ( Azzoni et al, 2018 ; Courville et al, 2020 ). However, our analyses showed that differences in community composition between years were stronger compared to differences between sites within years, especially considering phylogenetic community composition.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to previous studies, we observed significant variation in microbial community composition between years ( Chuvochina et al, 2011 ; Pittino et al, 2018 ; Els et al, 2020 ) and sites ( Azzoni et al, 2018 ; Courville et al, 2020 ). However, our analyses showed that differences in community composition between years were stronger compared to differences between sites within years, especially considering phylogenetic community composition.…”
Section: Discussionsupporting
confidence: 90%
“…Microbial communities were composed of similar groups of organisms as have been found in previous studies on mountain surface snow and ice in different parts of the globe (Segawa et al, 2005;Boetius et al, 2015;Maccario et al, 2015;Antony et al, 2016;Carey et al, 2016;Wunderlin et al, 2016;Azzoni et al, 2018;Zhou et al, 2019), including the European Alps (Chuvochina et al, 2011;Meola et al, 2015;Wunderlin et al, 2016;Azzoni et al, 2018;Courville et al, 2020;Els et al, 2020), and >10000year-old Himalayan glacial ice (Zhong et al, 2021). Dominant genera included known psychrophilic or psychrotolerant, UVresistant organisms typical for cryosphere environments such as heterotrophic Polaromonas (Gammaproteobacteria; Darcy et al, 2011) and Hymenobacter (Bacteroidia; Dai et al, 2009;Klassen and Foght, 2011;Sedláček et al, 2019), or photoautotrophs within the Chroococcidiopsidaceae (Cyanobacteria; Baqué et al, 2013).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Since the snow is coupled to the atmosphere, factors that affect airborne microbial communities, such as surrounding ecosystems and local meteorological conditions, could change the snow microbial community structure ( Tignat-Perrier et al, 2019 ; Els et al, 2020 ). At sites where trees are scarce, microbial life would be expected to colonize snow mainly from the atmosphere and dust and lead to a more even community ( Chuvochina et al, 2011 ; Courville et al, 2020 ). At sites with surrounding forest, the presence of trees might influence bacterial communities in two ways: (a) the phyllosphere community found on needles of trees could directly colonize the snow ( Lindow and Brandl, 2003 ; Rúa et al, 2016 ) and (b) tree litter could be a source of organic matter that would indirectly influence the growth of snow microorganisms ( Mahajan et al, 2016 ; Chae et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This process can reach intercontinental scale 7 , where airborne bacteria have been shown to remain viable and thrive after deposition in both marine [8][9][10] and terrestrial environments [11][12][13] . Large-scale aeolian dispersion and cell deposition have also been observed at distinct cryosphere habitats in the northern hemisphere [14][15][16][17] . Recently, a study suggested that microorganisms in marine aerosols over the Southern Ocean (SO), near the coastal East Antarctic Continent (EAC), were dominated by sea spray sources, with minimal contributions from other sources, such as Antarctic soils 18 .…”
Section: Introductionmentioning
confidence: 98%